Odpowiedzi

2009-11-23T18:32:50+01:00
A.
x2 + 2x + x +2 = x2 + 3x+2
b.
3a2 - 15a + 4a - 20 = 3a2 - 11a -20
c
2t - 6t2 + 1 - 3t = -6t2 - t +1
d
9ab-21a2b2 - 21 +49ab= -21a2b2 + 58ab - 21
e
- 5x2 - 6xy + 5xy + 6y2 = -5x2 + 6y2 - xy
f
7x2 - xy + 35xy - 5y2= 7x2 -5y2 + 34xy
g
2x8 + 2x4y - x4y - y2 = 2x8 + x4y -y2
h
2a2b2 + 6a2b - 2a2b - 6a2 = 2a2b2 - 4a2b - 6a2

:)
3 3 3
Najlepsza Odpowiedź!
2009-11-23T18:35:00+01:00
A) (x+1)(x+2) = x² + 2x + 2 +x = x² + 2 + 3x
b) (3a + 4)(a - 5) = 3a² - 15a + 4a - 20 = 3a² - 11a - 20
c) (2t + 1)(1-3t)= 2t - 6t² + 1 - 3t = -1t - 6t² + 1
d) (3ab - 7)(3 - 7ab)= 9ab - 21a²b² - 21 + 49ab = 58ab - 21a²b² - 21
e) (-x + y)(5x + 6y)= -5x - 6xy + 5xy + 6y²= -5x - xy + 6y²
f) (x + 5y)(7x - y)= 7x² - xy + 35xy - 5y²= 7x²- 34xy - 5y²
g) (2x⁴ - y)(x⁴ + y) = 2x⁸ + 2x⁴y - x⁴y - y²= 2x⁸ + x⁴y - y²
h) (ab - a)(2ab + 6a) = 2a²b² + 6a²b - 2a²b - 6a²= 6a²b - 6a²
4 3 4
2009-11-23T18:38:37+01:00
A. (x + 1)(x + 2)= x2+2x+x+2=3x+2+x2
b. (3a + 4)(a - 5)= 3a2-15a+4a-20=3a2-11a-20
c. (2t + 1)(1-3t)= 2t-6t2+1-3t=-7-6t2+1
d. (3ab - 7)(3 - 7ab)= 9ab-21a2b2-21+49ab=58ab-21a2b2-21
e. (-x + y)(5x + 6y)= -5x2-6xy+5xy+6y2=-5x2-xy+6y2
f. (x + 5y)(7x - y)= 7x2-xy+35xy-5y2=7x2+34xy-5y2
g. (2x⁴ - y)(x⁴ + y)= 2x4+2x4y-x4y-xy
h. (ab - a)(2ab + 6a)= 2a2b2+6a2b-2a2b-6a2=2a2b2-4a2b-6a2
2 5 2